The Relationship Between Work Environment Factors, Communication, And Teamwork with The Implementation of Patient Safety Culture - Ni Luh Putu Inca Buntari Agustini; Ni Komang Sri Wahyuni; I Nyoman Arya Mahaputra; Ni Made Manik Elisa Putri (Babali Nursing Research)
Introduction: A key component of quality management in the healthcare industry is the patient safety culture, which involves initiatives to prevent and reduce the likelihood of patient harm or injury during medical care. This literature review aims to explore the relationship between the implementation of a patient safety culture and factors such as work environment, communication, and teamwork.